Serbia and Оther Participants in the Balkan Theatre of War according to French Newspaper Le Petit Parisien in 1917. - Bajagić, Dušan (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The subject of the research is the writing of the French popular and high-circulated newspaper Le Petit Parisien (LPP) about Serbia and other participants in the Balkan theatre of war in 1917. The research aims is to classify the qualitative content of newspaper articles and their orientation. Efforts were made to find out how the newspaper reported about Serbia and the other participants in the Balkan theatre of war, how they were presented to the French public and what significance they had for France, other Allied Powers and Associated Allies. Basic analytical and synthetic methods were used in the research process. Of the general scientific methods, a hypothetical-deductive and historical method was applied. The results of this research confirmed that LPP wrote insignificantly little, almost imperceptibly, on Serbia and the other participants in the Balkan theatre of war, compared to all other, much more prevalent, reports on issues and events related to the Great War. The newspaper was exclusively interested in the loyalty and consistency of Serbia, the Allied Powers and Associated Allies on the Balkan theatre of war in the execution of military and political obligations that the Allies had determined in the struggle against the Central Powers. LPP did not attach any importance to other issues. Because of this, not much has been heard in public about the position of the Serb people under occupation and the condition of Serbian prisoners in the Central Powers camps.